Análise de tempos e movimentos aplicada em uma confeitaria localizada em Angicos - RN - Cunha, Maria Tatiana da (Universidade Federal Rural do Semi-Árido, 2019)
In a context of highly competitive labor market, micro enterprises are seeking ways to enhance their activities, optimizing mainly the process of production of its products, in order to appreciate the quality of the same. With this, standardize processes is essential to eliminate errors and unnecessary times. In this sense, the objective of this study was to conduct a time study in a micro company that operates in the confectionery sector in the municipality of Angicos/RN, with the purpose to suggest improvements to optimize the processes. In this way, the research was conducted in a first moment by lifting the theoretical framework, followed by the lifting the cakes which had a higher level of demand to map their processes, which were: the "Moça" cake, the merged and eggs cake and the carrot cake, then was applied the chronoanalysis technique. Thus, it was measured the pattern time of production of each cake, was subsequently proposed a new layout and held up the chronoanalysis in this new scenario. With the change in the layout, it was obtained a reduction in time production of 39% for the "Moça" cake, 34% for the merged and eggs cake and 0,1% for the carrot cake. With the acquisition of some equipment is expected to reduce even more these times.
Artigo
Keywords: Estudo de Tempos e Movimentos; Cronoanálise; Mapeamento de Processos; Confeitaria; Time and motion study; Chronoanalysis; Process mapping; Confectionery; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA